The Relationship Between the Tourism Industry and Sustainable Development Goals Word Cloud Analysis - Razvan-Catalin Dobrea; Aurel Marin; Cristina Dima; Madalina-Ioana Moncea (Amfiteatru Economic, 2023)
The worldwide adoption of sustainable models has been motivated by an increasing awareness of the negative environmental impacts caused by unsustainable economic development models. The paper explores the relationship between the tourism industry and sustainable development goals during the period 2015-2021, using 245 studies from the Google Academic database. Various approaches, such as Word Cloud analysis, correlation network, and word network, were used to identify frequently occurring words and word pairs in the research domain. The R software was used for this research. Empirical results were used to identify the most relevant journals in the field and the most prolific authors. The Journal of Sustainable Tourism addresses specific themes such as food , community , sanctions , and social . Sustainability focuses on culture , heritage , local , and environment , while the Worldwide Hospitality and Tourism Themes journal represents a niche in the field, covering topics such as community , health , well-being , investment , and growth . Thus, the results obtained can provide significant contributions to public policies and independently applied practices within the industry, facilitating more informed decision-making in support of sustainable development. This research contributes to the specialised literature by identifying current research trends in the tourism industry and its relationship with sustainable development goals, highlighting dominant themes based on the keywords used. These interdisciplinary connections can lead to deeper understanding and more efficient solutions for sustainable development
Keywords: L83; Q01; Q56; C87; C01; 330; Tourism; sustainable development goals; tourism journals; innovation; sustainability